Prognostic and Biologic Relevance of Clinically Applicable Long Non-Coding RNA Profiling in Older Patients with Cytogenetically Normal Acute Myeloid Leukemia - Papaioannou, Dimitrios (Mol Cancer Ther, 2019)
We have previously shown that expression levels of 48 long non-coding RNAs (lncRNAs) can generate a prognostic lncRNA score that independently associates with outcome of older patients with cytogenetically normal acute myeloid leukemia (CN-AML). However, the techniques used to identify and measure prognostic lncRNAs (i.e., RNA sequencing and microarrays) are not tailored for clinical testing. Herein we report on an assay (based on the nCounter platform) that is designed to produce targeted measurements of prognostic lncRNAs in a clinically applicable manner. We analyzed a new cohort of 76 older CN-AML patients and found that the nCounter assay yielded reproducible measurements and that the lncRNA score retained its prognostic value; patients with high lncRNA scores had lower complete remission (CR) rates (P=0.009; 58% vs. 87%), shorter disease-free (P=0.05; 3-year rates: 0% vs. 21%), overall (OS, P=0.02; 3-year rates: 10% vs. 29%) and event-free survival (EFS; P=0.002, 3-year rates: 0% vs. 18%) than patients with low lncRNA scores. In multivariable analyses, the lncRNA score independently associated with CR rates (P=0.02), OS (P=0.02) and EFS (P=0.02). To gain biological insights, we examined our initial cohort of 71 older CN-AML patients, previously analyzed with RNA sequencing. Genes involved in immune response and B-cell receptor signaling were enriched in patients with high lncRNA scores. We conclude that clinically applicable lncRNA profiling is feasible and potentially useful for risk stratification of older CN-AML patients. Furthermore, we identify potentially targetable molecular pathways that are active in the high-risk patients with high lncRNA scores.